A modified wollastonite with high aspect ratio and its preparation method and application

By covering and modifying wollastonite, the aspect ratio and compatibility with resin are improved, the problems of poor compatibility of wollastonite in resin matrix and structural damage during mechanical processing are solved, and higher product performance and cost reduction are achieved.

CN116253929BActive Publication Date: 2025-03-18JIANGXI GUANGYUAN CHEM +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211092382.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-08
Publication Date
2025-03-18
Estimated Expiration
2042-09-08

AI Technical Summary

Technical Problem

Wollastonite has poor compatibility in resin matrix and may lead to needle-like structure damage during machining.

Method used

By mixing the wollastonite suspension, dispersant and calcium nitrate solution, and adding sodium silicate solution for coating, amorphous calcium silicate-coated wollastonite was obtained, and the aspect ratio and compatibility with the resin were improved by calcining and modification treatment.

Benefits of technology

Improves the compatibility of wollastonite in resin matrix, improves its stability during machining, and reduces costs, and can partially or completely replace glass fibers in SMC and BMC.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of wollastonite, and in particular to a modified wollastonite with a high aspect ratio, and a preparation method and application thereof. The present invention provides a preparation method for modified wollastonite with a high aspect ratio, comprising the following steps: after mixing a wollastonite suspension, a dispersant and a calcium nitrate solution, adding a sodium silicate solution for coating to obtain amorphous calcium silicate-coated wollastonite; calcining the amorphous calcium silicate-coated wollastonite to obtain a high aspect ratio wollastonite fiber; mixing the high aspect ratio wollastonite with a transition metal ion solution, and performing a modification treatment to obtain the modified wollastonite with a high aspect ratio. The modified wollastonite with a high aspect ratio prepared by the preparation method has a higher aspect ratio, which can improve its compatibility in a resin matrix.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wollastonite, and in particular to a modified wollastonite with a high aspect ratio and a preparation method and application thereof. Background Art

[0002] Wollastonite is a chain metasilicate that is fibrous and needle-shaped. Due to its special crystal morphology and crystal structure, its properties are determined by wollastonite. It has good insulation, high whiteness, good dielectric properties, high heat resistance and weather resistance, and low cost. At the same time, sheet molding compound (SMC) and bulk molding compound (BMC) are generally used to manufacture low-end composite products, and cost control is relatively strict. Therefore, applying wollastonite to sheet molding compound (SMC) and bulk molding compound (BMC) can improve the flame retardant and insulation properties of the products while ensuring cost reduction. However, if wollastonite is directly added to the formulation system, there will be a problem of poor compatibility with the resin system; in addition, the needle-like structure of wollastonite may be destroyed during mechanical processing. Summary of the invention

[0003] The purpose of the present invention is to provide a modified wollastonite with a high aspect ratio, a preparation method and application thereof. The modified wollastonite with a high aspect ratio prepared by the preparation method has a higher aspect ratio and can improve its compatibility in a resin matrix.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a method for preparing modified wollastonite with a high aspect ratio, comprising the following steps:

[0006] After mixing the wollastonite suspension, the dispersant and the calcium nitrate solution, a sodium silicate solution is added for coating to obtain amorphous calcium silicate-coated wollastonite;

[0007] calcining the amorphous calcium silicate-coated wollastonite to obtain high aspect ratio wollastonite fibers;

[0008] The high aspect ratio wollastonite is mixed with a transition metal ion solution and subjected to modification treatment to obtain the modified wollastonite with a high aspect ratio.

[0009] Preferably, the mass concentration of the wollastonite suspension is 30-60%;

[0010] The particle size of wollastonite in the wollastonite suspension is 325-800 mesh;

[0011] The concentrations of the calcium nitrate solution and the sodium silicate solution are independently 50 to 150 mol / L.

[0012] Preferably, the molar ratio of calcium nitrate in the calcium nitrate solution to sodium silicate in the sodium silicate solution is 1:1;

[0013] The molar ratio of calcium nitrate in the calcium nitrate solution to wollastonite in the wollastonite suspension is (2-3):1;

[0014] The coating temperature is 20-40°C.

[0015] Preferably, the dispersant includes an inorganic dispersant or an organic dispersant;

[0016] The inorganic dispersant includes a silicate dispersant and / or an alkali metal phosphate dispersant;

[0017] The organic dispersant includes one or more of triethylhexyl phosphate, cellulose derivatives, sodium lauryl sulfate and fatty acid polyethylene glycol esters;

[0018] The mass percentage of the dispersant to the wollastonite in the wollastonite suspension is 1-5%.

[0019] Preferably, the calcination temperature is 800-1100° C., and the holding time is 1-5 hours.

[0020] Preferably, the concentration of the transition metal ion solution is 100-150 mol / L;

[0021] The molar ratio of transition metal ions in the transition metal ion solution to high aspect ratio wollastonite is (1-3):1.

[0022] Preferably, the transition metal ions in the transition metal ion solution are one or more of titanium ions, chromium ions, cobalt ions, nickel ions, copper ions, zinc ions and rare earth ions;

[0023] The modification treatment is carried out under stirring conditions, the temperature of the modification treatment is 100-130° C., and the stirring speed is 500-2000 rpm.

[0024] Preferably, after the modification treatment, the slurry obtained by the modification treatment is mixed with a modifier and then modified;

[0025] The functional group of the modifier includes one or more of an amide group, a carboxylic acid group, an ester group and an amine group.

[0026] The present invention also provides a modified wollastonite with a high aspect ratio prepared by the preparation method described in the above technical solution, wherein the aspect ratio of the modified wollastonite with a high aspect ratio is (12-18):1;

[0027] The hydroxyl groups on the surface of the high aspect ratio wollastonite in the modified wollastonite with a high aspect ratio are connected with the transition metal ions in the form of coordination bonds.

[0028] The present invention also provides the use of the modified wollastonite with a high aspect ratio described in the above technical solution in molding materials.

[0029] The invention provides a preparation method of modified wollastonite with a high aspect ratio, comprising the following steps: mixing a wollastonite suspension, a dispersant and a calcium nitrate solution, adding a sodium silicate solution for coating, and obtaining amorphous calcium silicate-coated wollastonite; calcining the amorphous calcium silicate-coated wollastonite to obtain a high aspect ratio wollastonite fiber; and mixing the high aspect ratio wollastonite with a transition metal ion solution, and performing a modification treatment to obtain the modified wollastonite with a high aspect ratio. The present invention uses wollastonite as a nucleating agent, sodium silicate and calcium nitrate as reaction raw materials, and induces the growth of its crystals in the length direction of the original wollastonite through high-temperature calcination. The aspect ratio of the original wollastonite is increased through heterogeneous nucleation to obtain wollastonite with a high aspect ratio. The surface of the wollastonite with a high aspect ratio is then modified, and the modified surface can form a coordination bond with a matrix resin, thereby improving the compatibility with the matrix resin and improving the comprehensive performance of the matrix resin. At the same time, the modified wollastonite with a high aspect ratio prepared by the preparation method can partially or completely replace the glass fiber in SMC and BMC, and the cost can be greatly reduced. DETAILED DESCRIPTION

[0030] The present invention provides a method for preparing modified wollastonite with a high aspect ratio, comprising the following steps:

[0031] After mixing the wollastonite suspension, the dispersant and the calcium nitrate solution, a sodium silicate solution is added for coating to obtain amorphous calcium silicate-coated wollastonite;

[0032] calcining the amorphous calcium silicate-coated wollastonite to obtain high aspect ratio wollastonite fibers;

[0033] The high aspect ratio wollastonite is mixed with a transition metal ion solution and subjected to modification treatment to obtain the modified wollastonite with a high aspect ratio.

[0034] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.

[0035] The invention mixes wollastonite suspension, dispersant and calcium nitrate solution, and then adds sodium silicate solution for coating to obtain amorphous calcium silicate-coated wollastonite.

[0036] In the present invention, the mass concentration of the wollastonite suspension is preferably 30-60%, more preferably 35-55%, and most preferably 40-50%. In the present invention, the particle size of the wollastonite in the wollastonite suspension is preferably 325-800 mesh, more preferably 400-600 mesh, and most preferably 450-550 mesh.

[0037] In the present invention, the wollastonite suspension is preferably obtained by preparation, and the preparation method of the wollastonite suspension preferably includes: mixing wollastonite with water. The present invention has no special limitation on the mixing process, and the process well known to those skilled in the art can be used.

[0038] In the present invention, the concentration of the calcium nitrate solution is preferably 50-150 mol / L, more preferably 60-80 mol / L, and most preferably 65-75 mol / L; the calcium nitrate solution is preferably prepared by, and the preparation method of the calcium nitrate solution preferably includes mixing calcium nitrate and water. The present invention has no special limitation on the mixing process, and the process well known to those skilled in the art can be used.

[0039] In the present invention, the dispersant preferably includes an inorganic dispersant or an organic dispersant; the inorganic dispersant preferably includes a silicate dispersant and / or an alkali metal phosphate dispersant; the organic dispersant preferably includes one or more of triethylhexyl phosphate, a cellulose derivative, sodium dodecyl sulfate and fatty acid polyethylene glycol esters; the silicate dispersant is preferably water glass; the alkali metal phosphate dispersant is preferably sodium tripolyphosphate and / or sodium hexametaphosphate; the cellulose derivative is preferably one or more of methyl cellulose, carboxymethyl cellulose and ethyl cellulose; the fatty acid polyethylene glycol ester is specifically preferably caprylic acid polyethylene glycol ester and / or capric acid polyethylene glycol ester; when the dispersant is two or more of the above-mentioned specific selections, the present invention has no special limitation on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio.

[0040] In the present invention, the molar ratio of calcium nitrate in the calcium nitrate solution to wollastonite in the wollastonite suspension is preferably (2-3):1, more preferably (2.2-2.8):1, and most preferably (2.4-2.6):1.

[0041] In the present invention, the mass percentage of the dispersant to the wollastonite in the wollastonite suspension is preferably 1-5%, more preferably 2-4%, and most preferably 2.5-3.5%.

[0042] In the present invention, the mixing is preferably performed by sequentially adding a calcium nitrate solution and a dispersant into a wollastonite suspension.

[0043] In the present invention, the concentration of the sodium silicate solution is preferably 50 to 150 mol / L, more preferably 60 to 80 mol / L, and most preferably 65 to 75 mol / L; the sodium silicate solution is preferably prepared by, and the preparation method of the sodium silicate solution preferably includes mixing sodium silicate and water. The present invention has no special limitation on the mixing process, and the process well known to those skilled in the art can be used.

[0044] In the present invention, the molar ratio of calcium nitrate in the calcium nitrate solution to sodium silicate in the sodium silicate solution is preferably 1:1.

[0045] In the present invention, the addition of the sodium silicate solution is preferably carried out under stirring. The present invention has no special limitation on the stirring process, and the stirring process can be carried out by a process well known to those skilled in the art. In the present invention, the sodium silicate solution is preferably added drop by drop. In the present invention, adding the sodium silicate solution drop by drop can further make it react with calcium nitrate step by step, and a layer of amorphous calcium silicate is covered on the surface of the wollastonite.

[0046] In the present invention, the coating temperature is preferably 20-40°C, more preferably 25-35°C; the coating time is preferably 3-4h; in the present invention, the coating time is preferably calculated based on the time when the sodium silicate aqueous solution is started to be added. In the present invention, the coating is preferably carried out under stirring conditions. The present invention does not have any special restrictions on the stirring conditions, and the conditions familiar to those skilled in the art can be used. After the coating is completed, the present invention also preferably includes filtration, and the filtration method is preferably suction filtration; the present invention does not have any special restrictions on the method and conditions of the suction filtration, and the method and conditions familiar to those skilled in the art can be used.

[0047] After obtaining the amorphous calcium silicate-coated wollastonite, the present invention calcines the amorphous calcium silicate-coated wollastonite to obtain high aspect ratio wollastonite fibers.

[0048] In the present invention, the calcination temperature is preferably 800-1100°C, more preferably 900-1000°C, and most preferably 930-960°C; the holding time is preferably 1-5h, more preferably 2-4h, and most preferably 2.5-3.5h. In the present invention, the calcination atmosphere is preferably a nitrogen atmosphere.

[0049] To obtain high aspect ratio wollastonite fiber, the high aspect ratio wollastonite is mixed with a transition metal ion solution and subjected to modification treatment to obtain the high aspect ratio modified wollastonite.

[0050] In the present invention, the concentration of the transition metal ion solution is preferably 100-150 mol / L, more preferably 110-140 mol / L, and most preferably 120-130 mol / L. In the present invention, the transition metal ions in the transition metal ion solution are preferably one or more of titanium ions, chromium ions, cobalt ions, nickel ions, copper ions, zinc ions and rare earth ions; the rare earth ions are preferably one or more of lanthanum ions, cerium ions, neodymium ions, europium ions and praseodymium ions; when the transition metal ions are two or more of the above-mentioned specific selections, the present invention has no special restrictions on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio. In the present invention, the solute in the transition metal ion solution is preferably an inorganic salt of a transition metal or an organic salt of a transition metal; the inorganic salt of the transition metal is preferably one or more of a chloride of a transition metal, a nitrate of a transition metal and a sulfate of a transition metal; the organic salt of the transition metal is preferably one or more of dibutyltin dilaurate, cyclopentadienyl cobalt and tricarbonyl iron. When the organic salt of the transition metal is two or more of the above-mentioned specific selections, the present invention has no special limitation on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio.

[0051] In the present invention, the molar ratio of transition metal ions in the transition metal ion solution to high aspect ratio wollastonite is preferably (1-3):1, more preferably (1.5-2.5):1, and most preferably (1.8-2.2):1.

[0052] In the present invention, the modification treatment is preferably carried out under stirring conditions. The present invention does not have any special restrictions on the stirring process, and the process well known to those skilled in the art can be used. In the present invention, the temperature of the modification treatment is preferably 100 to 130° C., more preferably 110 to 120° C.; the stirring speed is preferably 500 to 2000 rpm, more preferably 1000 to 1500 rpm.

[0053] In the present invention, the effect of the modification treatment is to form coordination bonds between the hydroxyl groups on the surface of the high aspect ratio wollastonite and the transition metal ions, so that the surface is completely coated with the transition metal ions.

[0054] After the modification treatment is completed, the present invention further preferably includes drying. In the present invention, the drying temperature is preferably 100-110°C, more preferably 102-108°C, and most preferably 103-106°C.

[0055] After the modification treatment is completed, the present invention preferably further comprises mixing the slurry obtained by the modification treatment with a modifier and then performing modification.

[0056] In the present invention, the functional group in the modifier preferably includes one or more of amide group, carboxylic acid group, ester group and amine group, and more preferably amide group.

[0057] In the present invention, the mass ratio of the high aspect ratio wollastonite to the modifier is preferably 1:(2-4), more preferably 1:3.

[0058] In the present invention, the modification temperature is preferably 60-80°C, more preferably 70°C; the modification time is preferably 3-5h, more preferably 3h.

[0059] After the modification is completed, the present invention also preferably includes sequentially performing filtration and drying. The present invention does not have any special limitation on the filtration and drying processes, and the filtration and drying processes well known to those skilled in the art can be used.

[0060] The present invention also provides a modified wollastonite with a high aspect ratio prepared by the preparation method described in the above technical solution, wherein the aspect ratio of the modified wollastonite with a high aspect ratio is (12-18):1;

[0061] The hydroxyl groups on the surface of the high aspect ratio wollastonite in the modified wollastonite with a high aspect ratio are connected with the transition metal ions in the form of coordination bonds.

[0062] The present invention also provides the use of the modified wollastonite with a high aspect ratio described in the above technical solution in a molding compound. In the present invention, the modified wollastonite with a high aspect ratio preferably partially replaces or completely replaces the glass fiber in SMC and BMC; the present invention does not have any special limitation on the method of the application, and the method well known to those skilled in the art can be used.

[0063] The modified wollastonite with a high aspect ratio and its preparation method and application provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0064] Example 1

[0065] After adding 500 mL of a 150 g / L calcium nitrate solution to 1000 mL of a 50% mass concentration wollastonite suspension, 10 g of an organosilicon dispersant (N,N-diethylethanolamine polyoxyalkyl ether and polysiloxane copolymer) was added, an equimolar sodium silicate aqueous solution with a concentration of 150 g / L was added dropwise under stirring, the mixture was reacted for 2 h, filtered, and dried to obtain amorphous calcium silicate-coated wollastonite;

[0066] In a nitrogen atmosphere, calcining the amorphous calcium silicate-coated wollastonite at 900° C. for 3 hours to obtain a high aspect ratio wollastonite fiber;

[0067] 1200 g of the high aspect ratio wollastonite and 100 mL of a 100 mol / L zinc naphthenate solution were mixed, treated at 110° C. for 3 h, filtered and dried to obtain modified wollastonite with a high aspect ratio.

[0068] According to the mass ratio of 100:20:80:10, 317 type unsaturated polyester resin, glass fiber, calcium carbonate and modified wollastonite with high aspect ratio were mixed to form a film to obtain an SMC sheet, which was laid, pressed and cured at 80°C for 2h to obtain an SMC sample;

[0069] According to the standard of GB / T 1040.1-2006, the tensile strength of the SMC sample was tested, and the test result showed that the tensile strength of the SMC sample was 28 MPa, which was 5 MPa higher than the tensile strength of the SMC sample prepared without the modified wollastonite with high aspect ratio (the mass ratio of 317 type unsaturated polyester resin, glass fiber and calcium carbonate was 100:30:80), and was equivalent to the tensile strength (30 MPa) of the SMC sample prepared by adding only glass fiber (the mass ratio of 317 type unsaturated polyester resin and glass fiber was 100:30), indicating that the mechanical properties of replacing 10 parts of glass fiber with 10 parts of modified wollastonite with high aspect ratio are equivalent, and the cost is reduced.

[0070] Example 2

[0071] After adding an equal volume of a 150 g / L calcium nitrate solution to 1000 mL of a 50% wollastonite suspension, 10 g of an organosilicon dispersant (N,N-diethylethanolamine polyoxyalkyl ether and polysiloxane copolymer) was added, an equal molar amount of a 150 g / L sodium silicate aqueous solution was added dropwise under stirring, the mixture was reacted for 2 h, filtered, and dried to obtain amorphous calcium silicate-coated wollastonite;

[0072] In an air atmosphere, calcining the amorphous calcium silicate-coated wollastonite at 900° C. for 3 hours to obtain a high aspect ratio wollastonite fiber;

[0073] 100 g of the high aspect ratio wollastonite was mixed with 200 mL of 100 mol / L zinc chloride solution, treated at 90° C. for 2 h, and then 30 g of stearic acid was added. The mixture was reacted for 1 h, filtered and dried to obtain modified wollastonite with a high aspect ratio.

[0074] According to the mass ratio of 100:20:80:10, 317 type unsaturated polyester resin, glass fiber, calcium carbonate and modified wollastonite with high aspect ratio were mixed to form a film to obtain an SMC sheet, which was laid, pressed, and cured at 80°C for 2h to obtain and prepare an SMC sample;

[0075] According to the standard of GB / T 1040.1-2006, the tensile strength of the SMC sample was tested. The test result showed that the tensile strength of the SMC sample was 31 MPa, which was slightly higher than that of Example 1, indicating that further treatment with stearic acid improved the compatibility in the wollastonite polyester resin system and improved the mechanical properties; the tensile strength (30 MPa) was slightly higher than that of the SMC sample prepared by adding only glass fiber (the mass ratio of 317 unsaturated polyester resin to glass fiber was 100:30).

[0076] Example 3

[0077] After adding an equal volume of a 150 g / L calcium nitrate solution to 1000 mL of a 100 g / L wollastonite suspension, 10 g of an organosilicon dispersant (N,N-diethylethanolamine polyoxyalkyl ether and polysiloxane copolymer) was added, an equal molar amount of a 150 g / L sodium silicate aqueous solution was added dropwise under stirring, the mixture was reacted for 2 h, filtered, and dried to obtain amorphous calcium silicate-coated wollastonite;

[0078] In an air atmosphere, calcining the amorphous calcium silicate-coated wollastonite at 900° C. for 3 hours to obtain a high aspect ratio wollastonite fiber;

[0079] 100 g of the high aspect ratio wollastonite and 200 mL of 150 mol / L lanthanum chloride solution were mixed, treated at 90° C. for 2 h, 30 g of stearic acid was added, reacted for 1 h, filtered and dried to obtain modified wollastonite with a high aspect ratio.

[0080] According to the mass ratio of 100:20:80:10, 317 type unsaturated polyester resin, glass fiber, calcium carbonate and modified wollastonite with high aspect ratio were mixed to form a film to obtain an SMC sheet, which was laid, pressed, and cured at 80°C for 2h to obtain and prepare an SMC sample;

[0081] According to the standard of GB / T 1040.1-2006, the tensile strength of the SMC sample was tested, and the test result showed that the tensile strength of the SMC sample was 30 MPa.

[0082] Example 4

[0083] After adding an equal volume of a 150 g / L calcium nitrate solution to 1000 mL of a 100 g / L wollastonite suspension, 10 g of an organosilicon dispersant (N,N-diethylethanolamine polyoxyalkyl ether and polysiloxane copolymer) was added, an equal molar amount of a 150 g / L sodium silicate aqueous solution was added dropwise under stirring, the mixture was reacted for 2 h, filtered, and dried to obtain amorphous calcium silicate-coated wollastonite;

[0084] In a nitrogen atmosphere, calcining the amorphous calcium silicate-coated wollastonite at 900° C. for 2 hours to obtain a high aspect ratio wollastonite fiber;

[0085] 100 g of the high aspect ratio wollastonite and 200 mL of 100 mol / L zinc cyclohexane solution were mixed, treated at 110° C. for 3 h, and then 20 g of phosphate was added at 80° C. for 1 h, filtered and dried to obtain modified wollastonite with a high aspect ratio.

[0086] According to the mass ratio of 100:20:80:10, 317 type unsaturated polyester resin, glass fiber, calcium carbonate and modified wollastonite with high aspect ratio were mixed into a film to obtain an SMC sheet, which was laid, pressed, and cured at 80°C for 2h to obtain an SMC sample;

[0087] According to the standard of GB / T 1040.1-2006, the flame retardant performance of the SMC sample was tested. The test result showed that the oxygen index of the SMC sample was 27%, which was significantly improved compared with 17.4% of Example 3.

[0088] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing modified wollastonite with a high aspect ratio, characterized in that: The following steps are involved: After mixing the wollastonite suspension, the dispersant and the calcium nitrate solution, a sodium silicate solution is added for coating to obtain amorphous calcium silicate-coated wollastonite; calcining the amorphous calcium silicate-coated wollastonite to obtain high aspect ratio wollastonite fibers, wherein the calcination temperature is 900° C.; The high aspect ratio wollastonite fiber is mixed with a transition metal ion solution and subjected to modification treatment to obtain the high aspect ratio modified wollastonite.

2. The preparation method according to claim 1, characterized in that The mass concentration of the wollastonite suspension is 30-60%; The particle size of wollastonite in the wollastonite suspension is 325-800 mesh; The concentrations of the calcium nitrate solution and the sodium silicate solution are independently 50 to 150 mol / L.

3. The preparation method according to claim 1 or 2, characterized in that: The molar ratio of calcium nitrate in the calcium nitrate solution to sodium silicate in the sodium silicate solution is 1:1; The molar ratio of calcium nitrate in the calcium nitrate solution to wollastonite in the wollastonite suspension is (2-3):1; The coating temperature is 20-40°C.

4. The preparation method according to claim 1, characterized in that: The dispersant includes an inorganic dispersant or an organic dispersant; The inorganic dispersant includes a silicate dispersant and / or an alkali metal phosphate dispersant; The organic dispersant includes one or more of triethylhexyl phosphate, cellulose derivatives, sodium lauryl sulfate and fatty acid polyethylene glycol esters; The mass percentage of the dispersant to the wollastonite in the wollastonite suspension is 1-5%.

5. The preparation method according to claim 1, characterized in that: The calcination holding time is 1 to 5 hours.

6. The preparation method according to claim 1, characterized in that: The concentration of the transition metal ion solution is 100-150 mol / L; The molar ratio of transition metal ions in the transition metal ion solution to the high aspect ratio wollastonite fibers is (1-3):

1.

7. The preparation method according to claim 6, characterized in that: The transition metal ion in the transition metal ion solution is one or more of titanium ion, chromium ion, cobalt ion, nickel ion, copper ion, zinc ion and rare earth ion; The modification treatment is carried out under stirring conditions, the temperature of the modification treatment is 100-130° C., and the stirring speed is 500-2000 rpm.

8. The preparation method according to claim 1 or 7, characterized in that: After the modification treatment, the method further comprises mixing the slurry obtained by the modification treatment with a modifier and performing modification; The functional groups in the modifier include one or more of amide groups, carboxylic acid groups, ester groups and amine groups.

9. The modified wollastonite with a high aspect ratio prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The aspect ratio of the modified wollastonite with a high aspect ratio is (12-18):1; The hydroxyl groups on the surface of the high aspect ratio wollastonite in the modified wollastonite with a high aspect ratio are connected with the transition metal ions via coordination bonds.

10. Use of the modified wollastonite with a high aspect ratio as claimed in claim 9 in molding compounds.

Citation Information

Patent Citations

  • Method for preparing modified acicular wollastonite

    CN101774594A

  • Preparation method of ultra-fine wollastonite with high length-diameter ratio

    CN111943217A

  • Porous calcium silicate loaded rare earth ion filler powder and preparation method thereof

    CN111995882A